Powdery mildew caused by Erysiphe corylacearum: An emerging problem on hazelnut in Italy. - Slavica Matić; Andrea G Caruso; Chiara D'Errico; Camilla Sacco Botto; Emanuela Noris; Vojislav Trkulja; Stefano Panno; Salvatore Davino; Marco Moizio (PLoS ONE)
Erysiphe corylacearum has recently been reported in northern Italy (Piedmont) and other European countries as the causal agent of a new emerging powdery mildew on hazelnut. This disease is much more dangerous than the common hazelnut powdery mildew caused by Phyllactinia guttata as it significantly reduces yield and quality of hazelnuts. This study aimed to perform morphological and molecular characterization of the fungal isolates from powdery mildew-infected plants in the Piedmont Italian region. Additionally, genetic diversity studies and pathogenicity tests were conducted. Thirty-six fungal isolates originating from symptomatic hazelnut plants exhibiting specific powdery mildew symptoms on the superior leaf side were identified morphologically as E. corylacearum. Single- and multilocus sequence typing of five loci (ITS, rpb2, CaM, GAPDH and GS) assigned all isolates as E. corylacearum. Multilocus and GAPDH phylogenetic studies resulted in the most efficient characterization of E. corylacearum. Studied fungal isolates were able to cause new emerging powdery mildew disease by fulfilling Koch's postulates. The emergence of powdery mildew disease in Italy revealed the E. corylacearum subgrouping, population expansion, and high nucleotide similarity with other recently identified E. corylacearum hazelnut isolates. To contain this harmful disease and inhibit the fungus spread into new geographical zones, it will be necessary to implement more rigorous monitoring in neighboring hazelnut plantations near infected hazelnuts, use sustainable fungicides and search for new biocontrol agents.